2019
DOI: 10.1371/journal.pone.0223008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lyse-It on endonuclease fragmentation, function and activity

Abstract: Nucleases are enzymes that can degrade genomic DNA and RNA that decrease the accuracy of quantitative measures of those nucleic acids. Here, we study conventional heating, standard microwave irradiation, and Lyse-It, a microwave-based lysing technology, for the potential to fragment and inactivate DNA and RNA endonucleases. Lyse-It employs the use of highly focused microwave irradiation to the sample ultimately fragmenting and inactivating RNase A, RNase B, and DNase I. Nuclease size and fragmentation were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The level of fragmentation is dependent on MW power and irradiation time. An increase in either MW power or exposure time results in an increase in fragmentation [31].…”
Section: Microwave-based Molecular Diagnosticsmentioning
confidence: 99%
“…The level of fragmentation is dependent on MW power and irradiation time. An increase in either MW power or exposure time results in an increase in fragmentation [31].…”
Section: Microwave-based Molecular Diagnosticsmentioning
confidence: 99%
“…This method of lysing DNA is much quicker than the current diagnostic DNA extraction methods and could be incorporated into point of care diagnostics. However, crucially there are currently no benefits in sensitivity as the samples are contaminated by the microwaved gold, and currently, due to the cost of the Lyse It Slides this method is not yet suitable to be used as a common DNA extraction method within diagnostic laboratories [ 64 , 65 ].…”
Section: Healthcare Developmentsmentioning
confidence: 99%
“…Geddes et al have taken a similar approach by developing a lysis setup of planar metal structures on a glass substrate called microwave lysing triangles (MLTs) or Lyse-It ® devices that utilize a common radio frequency (RF)/microwave source (300 MHz–300 GHz), microwave ovens, to prepare clinical samples for downstream detection in 30–60 s, as depicted in Figure 9 [ 125 , 129 , 130 , 131 , 132 ]. The utility of this approach comes from several of the factors needed for POC sample preparation methods such as simple operation, minimal equipment requirements, and lack of cold chain requirements for samples treated with MLTs, as well as the ability to fragment common target biomarkers such as nucleic acids, enzymes, and proteins in a tunable manner for downstream analysis [ 133 , 134 , 135 , 136 ]. While similar extraction techniques, termed microwave-assisted extraction (MAE), have found use with environmental, geological, and biological samples [ 137 , 138 , 139 ], some researchers such as Ahirwar et al have reported using microwave irradiation to reduce the time needed for diagnostic ELISAs from 2 h to less than 5 min via non-thermal effects [ 140 ].…”
Section: Integrated and Portable Sample Preparation Devicesmentioning
confidence: 99%
“…The rapid heating, focused electric field intensity, and reactive oxygen species (ROS) responsible for lysis arise from the incident microwave photons. From Geddes et al [ 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ].…”
Section: Figurementioning
confidence: 99%